β-Cyclodextrin and Oligoarginine Peptide-Based Dendrimer-Entrapped Gold Nanoparticles for Improving Drug Delivery to the Inner Ear - Luo, Jia; Lin, XueXin; Li, LiLing; Tan, JingQian; Li, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
Here, we developed a safe and highly effective nanocarrier using β-cyclodextrin (β-CD) and oligoarginine peptide (Arg8)-modified dendrimer-entrapped gold nanoparticles (Au@CD-PAMAM-Arg8), with a diameter of 5 nm, for improved delivery of dexamethasone (Dex) to the inner ear. The properties and in vivo distribution of the Au@CD-PAMAM-Arg8 were assessed in vitro, and a streptomycin (SM) ototoxicity model was used in vivo. Flow cytometry analysis of HEIOC1 cells treated with Au@CD-PAMAM-Arg8 and Au @CD-PAMAM at different time intervals indicated that cell uptake efficiency of the drug delivery carrier Au@CD-PAMAM-Arg8 was higher than that of Au @CD-PAMAM. Au@CD-PAMAM-Arg8 carrying Dex (Au@CD-PAMAM-Arg8/Dex) were mainly distributed in hair cells, the spiral ganglion, lateral wall, and nerve fibers and had stronger protective effects on the inner ear than Dex administration alone. In vivo tracer tests revealed that tympanic injection was significantly more effective than posterior ear injection, muscle injection, and tail vein injection, whereas clinical retro-auricular injection could not increase the efficiency of drug delivery into the ear. Electrocochleography results showed that Au@CD-PAMAM-Arg8/Dex significantly improved hearing in C57/BL6 mice after SM exposure. These findings indicate that Au@CD-PAMAM-Arg8 may be the useful drug carriers for the treatment of inner ear diseases.